Contrast Induced Nephropathy in Patients with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention - Shah Muhammad Babar, Khawar Abbas Kazmi, Javed Majid Tai, Faraz Farooq Memon, Saadia Uzair, Saira Bukhari, Saad Muhammad Babar, Mustafa Ghilzai, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of contrast induced nephropathy in patients with acute coronary syndrome undergoing percutaneous coronary intervention. Material & Methods: This study was conducted on all patients underwent percutaneous coronary intervention between the age of 20 years to 70 years at the Department of Cardiology, Aga Khan University Hospital, Karachi. Percutaneous coronary intervention was performed as per latest ESC guidelines and frequency of CIN was observed among all patients through comparing renal function test from baseline to post-procedure. Results: A total of 237 patients were included. 180 patients (75.9%) were males & 57 (24.1%) were females, with mean age of 58.94±11.49 years. The mean BMI was 26.76±5.40 kg/m2. 107 patients (45.1%) had DM, 153 (64.6%) were hypertensive and 100 (42.2%) had left ventricular dysfunction. 205 (86.1%) were in Killip class 1 and 33 (13.9%) were in Killip class 2. The mean pre PCI creatinine was 0.88±0.20 mg/dl. Type of contrast was non-ionic in 235 patients (99.2%). The mean volume of contrast was 201.18±79.15 ml. The mean post PCI (48 hours) creatinine was 0.95±0.27 mg/dl. Contrast induced nephropathy was seen in 5 patients (2.1%) Conclusion: The frequency of Contrast induced nephropathy in our study was much lower but measures should be taken to further minimize such complication in which patient's quality of life and may be compromised with subsequently higher mortality rates.